How does narcissistic leadership influence change-oriented organizational citizenship behavior? Empirical evidence from China - Yangchun Fang; Yonghua Liu; Peiling Yu; Nuo Chen (Humanities & Social Sciences Communications)
Abstract Based on conservation of resources theory and the work–home resources model, this study examines how and when narcissistic leadership influences employees’ change-oriented organizational citizenship behavior. A total of 363 employees from 61 teams across numerous enterprises based in central China were surveyed using a questionnaire. The study hypotheses were tested using structural equation modeling and Monte Carlo simulation analysis. The findings revealed that narcissistic leadership results in the development of a negative team climate, termed “team chaxu climate,” which, in turn, hinders employees’ change-oriented organizational citizenship behavior. Furthermore, this study explored the moderating role of leaders’ family affective support in the relationship between narcissistic leadership and team chaxu climate. This study contributes to our understanding of the relationship between narcissistic leadership and employee organizational citizenship behavior and empirically validates the work–home resources model.